2002
DOI: 10.1046/j.1470-6431.2002.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Buyer–seller relationships for promotional support in the apparel sector

Abstract: Promotional supports provided by manufacturers are important to many retailers. With the intense competition for customers and heightened concern for profit margins, retailers’ cooperation is critical in the promotional process so that promotional services mutually benefit both manufacturers and retailers. The purpose of this study was to define promotional support categories offered to apparel retailers from manufacturers, to identify the retailer's perceptions of the offering frequency and importance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These unique characteristics of luxury fashion products combined with the increasing economic significance of the sector globally provide justification for research into the decision-making process of luxury fashion retail buyers, which is central to the success or failure of the retail store. Existing literature is focused on the grocery (Sternquist and Chen, 2006;Johansson and Burt, 2004) and mid-market fashion sectors (Bruce and Daly, 2006;Goworek, 2010) in large companies such as department store chains (Fairhurst and Fiorito, 1990;Entwistle, 2006;Stone and Cassill, 1989;Wall et al, 1994) and large retail chains (Goworek, 2010;da Silva et al, 2002;Kincade et al, 2002;Wall et al, 1994;Stone and Cassill, 1989;Banting and Blenkhorn, 1988). Previous literature has focused on US apparel retailers and there is a lack of research on whether Sheth's (1981) model equally applies to European apparel retailers.…”
Section: The Luxury Fashion Marketmentioning
confidence: 99%
See 3 more Smart Citations
“…These unique characteristics of luxury fashion products combined with the increasing economic significance of the sector globally provide justification for research into the decision-making process of luxury fashion retail buyers, which is central to the success or failure of the retail store. Existing literature is focused on the grocery (Sternquist and Chen, 2006;Johansson and Burt, 2004) and mid-market fashion sectors (Bruce and Daly, 2006;Goworek, 2010) in large companies such as department store chains (Fairhurst and Fiorito, 1990;Entwistle, 2006;Stone and Cassill, 1989;Wall et al, 1994) and large retail chains (Goworek, 2010;da Silva et al, 2002;Kincade et al, 2002;Wall et al, 1994;Stone and Cassill, 1989;Banting and Blenkhorn, 1988). Previous literature has focused on US apparel retailers and there is a lack of research on whether Sheth's (1981) model equally applies to European apparel retailers.…”
Section: The Luxury Fashion Marketmentioning
confidence: 99%
“…The nature of fashion retail buying Retail buying can be defined as the decision-making process by which individuals in an organisation establish end consumer requirements for products and subsequently identify, evaluate and select among alternative brands and suppliers (Kincade et al, 2002). For a fashion retail brand, buyers select own-label product from a range of garment suppliers, while for independent fashion retailers, buyers select branded product from range of fashion brands.…”
Section: Fashion Retail Buyers In Greecementioning
confidence: 99%
See 2 more Smart Citations
“…Next, we briefly review several papers concerning the coordination of fashion supply chains. Kincade et al (2002) conducted a survey and revealed that the benefits of retailers in the apparel industry are greatly related to the financial promotional support from manufacturers. Motivated by a real case in the apparel industry, Eppen and Iyer (1997) developed a stochastic dynamic programming model to investigate a backup agreement for a fashion supply chain involving a catalog company and a manufacturer.…”
Section: Introductionmentioning
confidence: 99%